MINAT PASANGAN USIA SUBUR MEMAKAI ALAT KONTRASEPSI DALAM RAHIM - Hajar Nur Fathur Rohmah; Wiwin Widia Sari (Jurnal Ilmiah Maternal, 2019)
ABSTRACT One contraceptive tool that has a high effectiveness in controlling the rate of population growth is Intra Uterin Device (IUD) reaching 99.4% (BKKBN, 2015). A preliminary survey conducted at RB Rhaudatunnadya, Bekasi said that only 0.6% of women of Fertile Age Couple chose the IUD method to manage their pregnancy. From interviews with women of Fertile Age Couple, 95% were not interested in using an IUD. Interest is very influential on how someone does something. Interest in family planning acceptors can be influenced by several factors including knowledge, parity, income and husband’s support. The research design used in this study is quantitative analytic using the cross sectional approach. The population of this research is the woman of the Fertile Age Couple in RB Raudhatunnadya with a total sample of 177 people taken by accidental sampling technique in RB Raudhatunnadya, Bekasi in 2019. Data in this study were obtained through a closed questionnaire. Univariate analysis uses percentages while bivariate analysis is done with chi square. The results showed there was a correlation between knowledge with Fertile Age Couple interest in using an IUD (p = 0,000, OR = 3,396), there was a correlation between parity with Fertile Age Couple interest in using an IUD (p = 0.048, OR = 3.106), there was a correlation between income with an Fertile Age Couple interest in using an IUD (p = 0.024, OR = 2.090) and there is a correlation between husband’s support and Fertile Age Couple interest in using an IUD (p = 0.012, OR = 2.317). Fertile age couple knowledge of both husband and wife needs to be improved by health workers by providing better counseling so that the wife is more able to use the IUD with the support of a husband who already has sufficient knowledge of the IUD. Keywords: Interests, Fertile Age Couple, IUD ABSTRAK Salah satu alat kontrasepsi yang mempunyai efektifitas tinggi mengendalikan laju pertumbuhan penduduk adalah alat kontrasepsi dalam rahim (AKDR) mencapai 99,4% (BKKBN, 2015). Survei pendahuluan yang dilakukan di RB Rhaudatunnadya, Bekasi menyebutkan hanya 0,6% wanita usia subur memilih metode AKDR untuk mengatur kehamilannya. Dari hasil wawancara kepada wanita usia subur menyatakan 95% tidak berminat menggunakan AKDR. Minat sangat berpengaruh terhadap bagaimana seseorang melakukan sesuatu aktivitas. Minat akseptor KB dapat dipengaruhi oleh beberapa faktor diantaranya pengetahuan, paritas, pendapatan dan dukungan suami. Desain penelitian yang digunakan dalam peneliti ini adalah analitik kuantitatif menggunakan pendekatan Cross sectional. Populasi penelitian ini adalah Wanita dari Pasangan Usia Subur di RB Raudhatunnadya dengan jumlah sample sebanyak 177 orang yang diambil dengan teknik accidental sampling di RB Raudhatunnadya, Bekasi tahun 2019. Data dalam penelitian ini diperoleh melalui kuesioner tertutup. Analisis univariat menggunakan prosentase sedangkan analisis bivariat dilakukan dengan chi square. Hasil penelitian menunjukkan ada hubungan antara pengetahuan dengan minat PUS memakai AKDR (p = 0,000, OR=3,396), ada hubungan antara paritas dengan minat PUS memakai AKDR (p=0,048, OR=3,106), ada hubungan antara pendapatan dengan minat PUS memakai AKDR (p=0,024, OR=2,090) dan ada hubungan antara dukungan suami dengan minat PUS menggunakan AKDR (p=0,012, OR=2,317). Pengetahuan PUS baik suami dan istri perlu ditingkatkan oleh tenaga kesehatan dengan pemberian konseling yang lebih baik lagi sehingga istri makin mantab memakai AKDR dengan dukungan suami yang telah mempunyai pengetahuan yang cukup menganai AKDR. Kata Kunci: Minat, Pasangan Usia Subur, Alat Kontrasepsi Dalam Rahim